2015
DOI: 10.1002/ange.201411450
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Shell Carbon‐Encapsulated Iron Nanoparticles: Synthesis and High Electrocatalytic Activity for Hydrogen Evolution Reaction

Abstract: Efficient hydrogen evolution reaction (HER) through effective and inexpensive electrocatalysts is avaluable approach for clean and renewable energy systems.Here,singleshell carbon-encapsulated iron nanoparticles (SCEINs) decorated on single-walled carbon nanotubes (SWNTs) are introduced as an ovel highly active and durable non-noble-metal catalyst for the HER. This catalyst exhibits catalytic properties superior to previously studied nonprecious materials and comparable to those of platinum. The SCEIN/SWNT is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 43 publications
(29 reference statements)
3
36
0
2
Order By: Relevance
“…Furthermore, our calculations predicted that a thinner layer would be better for ORR in M@N-C nanoparticles. 27,44,45 These tendencies are consistent with previous reports that the thinner layer of carbon leads to higher activity in the FeCo alloy catalyst encapsulated in pod-like carbon nanotubes. Moreover, a particle encapsulated with a single layer of carbon has also been used as a HER and OER catalyst with superior activity.…”
Section: Thickness Of Carbon Shells For Orr Activitysupporting
confidence: 91%
“…Furthermore, our calculations predicted that a thinner layer would be better for ORR in M@N-C nanoparticles. 27,44,45 These tendencies are consistent with previous reports that the thinner layer of carbon leads to higher activity in the FeCo alloy catalyst encapsulated in pod-like carbon nanotubes. Moreover, a particle encapsulated with a single layer of carbon has also been used as a HER and OER catalyst with superior activity.…”
Section: Thickness Of Carbon Shells For Orr Activitysupporting
confidence: 91%
“…The XPS results for Co/AC only revealed the binding energy of Co II species, which demonstrated that surface‐exposed Co NPs were facile to oxidize. Moreover, the binding energy of encapsulated metallic cobalt is higher than that of bulk Co NPs (778.0 eV) by 0.4 eV; this is consistent with charge transfer from the encapsulated Co metal to the carbon shells; thus the electrical levels of cobalt and carbon atoms were modified. It has been reported that the interaction of N‐doped carbon nanotubes (N‐CNTs) and confined Co could increase the density of states (DOS) near the Fermi level and reduce the work function ( Φ ), which is beneficial for donating electrons from the surface of N‐CNTs to surface‐adsorbed molecular oxygen, thereby enabling the Co 4 @CNTs to be an outstanding electrocatalytic catalyst in the ORR .…”
Section: Resultssupporting
confidence: 55%
“…For instances, Ni−Sn@C core/shell structure was synthesized by combining sol−gel, chemical vapor deposition (CVD) and etching processes 63 . Tavakkoli et al 64 used single-walled CNTs as the carbon shell to encapsulate Fe nanoparticles by CVD technique (Fig. This core/shell catalyst had a high conductivity and large active surface area and exhibited good electrocatalytic activity toward HER.…”
Section: Noble Metal-free Compositesmentioning
confidence: 99%